Penguatan Literasi Digital Pada Siswa SD Melalui Implementsi Game Based Learning (GBL) - Ayulia, Ervina; Perdana, Parrisca Indra (Educational Consultant & Counseling Career (EC3) Mataram, 2022)
The study focused on digital literacy education through game based learning to enhance the digital literacy of underrated east 1 kamal class 4 students. Literacy in this study is the basic literacy of reading and writing molded in digital. The negative impact of digital literacy is not using digital for learning activities but digital is used to play games or access the various content of social media. From here teachers are thinking of turning such negative habits into positives with learning activities through games based learning. Based on the results of these discussions, it may be concluded that learning activities through games based learning can improve digital literacy in students. This can be seen from the results of observation and assessment of as many as 20 students or as much as 80% (14 students) of the digital literacy increased. In addition, students are more interested in and enjoy learning activities using video games.